Verification and Analysis of Sheep Tail Type-Associated PDGF-D Gene Polymorphisms - Qing Li; Zengkui Lu; Meilin Jin; Xiaojuan Fei; Kai Quan; Yongbin Liu; Lin Ma; Mingxing Chu; Huihua Wang; Caihong Wei (Animals, 2020)
The aim of this study was to examine the correlation between the platelet-derived growth factor-D (PDGF-D) gene and sheep tail type character and explore the potential underlying mechanism. A total of 533 sheep were included in this study. Polymorphic sites were examined by Pool-seq, and individual genotype identification and correlation analysis between tail type data were conducted using the matrix-assisted laser desorption/ionization time-of-flight mass spectrometer (MALDI-TOF-MS) method. JASPART website was used to predict transcription factor binding sites in the promoter region with and without PDGF-D gene mutation. The effect of PDGF-D on adipogenic differentiation of sheep preadipocytes was investigated. Two single nucleotide polymorphism sites were identified: g.4122606 C > G site was significantly correlated with tail length, and g.3852134 C > T site was significantly correlated with tail width. g.3852134 C > T was located in the promoter region. Six transcription factor binding sites were eliminated after promoter mutation, and three new transcription factor binding sites appeared. Expression levels of peroxisome proliferator-activated receptor gamma (PPARγ) and lipoproteinlipase (LPL) were significantly up-regulated upon PDGF-D overexpression. Oil red O staining showed increased small and large oil drops in the PDGF-D overexpression group. Together these results indicate the PDGF-D gene is an important gene controlling sheep tail shape and regulating sheep tail fat deposition to a certain degree.